Atomic structure calculations and identification of EUV and SXR spectral lines in Sr XXX. (August 2015) - Goyal, Arun; Khatri, Indu; Aggarwal, Sunny; Singh, A.K.; Mohan, Man
Abstract: We report an extensive theoretical study of atomic data for Sr XXX in a wide range with L-shell electron excitations to the M-shell. We have calculated energy levels, wave-function compositions and lifetimes for lowest 113 fine structure levels and wavelengths of an extreme Ultraviolet (EUV) and soft X-ray (SXR) transitions. We have employed multi-configuration Dirac Fock method (MCDF) approach within the framework of Dirac–Coulomb Hamiltonian including quantum electrodynamics (QED) and Breit corrections. We have also presented the radiative data for electric and magnetic dipole (E1, M1) and quadrupole (E2, M2) transitions from the ground state. We have made comparisons with available energy levels compiled by NIST and achieve good agreement. But due to inadequate data in the literature, analogous relativistic distorted wave calculations have also been performed using flexible atomic code (FAC) to assess the reliability and accuracy of our results. Additionally, we have provided new atomic data for Sr XXX which is not published elsewhere in the literature and we believe that our results may be beneficial in fusion plasma research and astrophysical investigations and applications. Highlights: 113 Lowest levels for Sr XXX are calculated. Extreme Ultraviolet (EUV) and soft-X ray (SXR) spectral lines are identified. Wavelengths of EUV and SXR spectral lines are reported. E1, E2, M1 and M2 transition rates, oscillator strengths and lines strengths for lowest 113 levels are presented. Lifetimes for lowest 113 fine structure levels are provided.